Teacher Communication Culture In The Class - G. Turgunova; Sh. Mamasidikova (Research Parks Publishing LLC, 2021)
Today, our independent republic is recognized by the world community, and its further development and prosperity depends on today's youth. This means that today's young people are able to express their right attitude to themselves, to other people, to society, to nature and to work, which is fully developed. Must be able to work independently, be creative, enterprising and resourceful. The development of these qualities in the student definitely depends on the teacher, his ability to properly manage the educational process and the relationships and interactions he can establish with students